Heat transfer and fluid flow characteristics of synthetic jets - Jagannatha, Deepak (Curtin University, 2009)
This thesis presents a fundamental research investigation that examines the thermal and fluid flow behaviour of a special pulsating fluid jet mechanism called synthetic jet. It is envisaged that this novel heat transfer enhancement strategy can be developed for high-performance heat sinks in electronic cooling applications.The study considers a unique arrangement of a periodic jet induced by diaphragm motion within a cavity and mounted on a confined flow channel with a heated wall upon which the jet impingement occurs. The operation of this jet mechanism is examined as two special cases for unravelling its parametric influences. In Case (a), the jet impingement is analysed in a channel with stagnant fluid permitting clear view of the pure synthetic jet process and its controlling variables. In Case (b), jet impingement is considered with fluid flow in the channel to establish the nature of synthetic jet and cross-flow interaction.The unsteady flow of this jet mechanism is simulated as a time-dependant two-dimensional numerical model with air as the working fluid. The current model considers a solution domain in its entirety, comprising the confined flow regions of the jet impinging surface, the cavity and the orifice. With a User Defined Function (UDF), the model accounts for the bulk fluid temperature variations during jet operation, which has been grossly ignored in all published work. Overcoming previous modelling limitations, the current simulation includes flow turbulence for realistic representation of pulsed jet characteristics and cross-flow interference.Computations are performed with applicable boundary conditions to obtain the heat transfer and fluid flow characteristics of the synthetic jet along with cross-flow interaction for the diaphragm amplitude ranging from 0.5 mm to 2 mm and the diaphragm frequency varying from 250 Hz to 1000 Hz. The numerical simulation yields stable solutions and aptly predicts the sequential formation of synthetic jet and its intrinsic vortex shedding process while accurately portraying the flow within the cavity.It is identified that the diaphragm amplitude primarily determines the jet velocity while the diaphragm frequency governs the rate of vortex ejection and the fluid circulation in the vicinity of the heater. The synthetic jet thermal performance is improved with high amplitude that gives rise to stronger jet impingement and reduced bulk fluid temperature arising from high frequency leading to better fluid circulation. The fluid flow in the channel or cross flow drags the jet downstream affecting jet’s ability to reach the heated wall. The relative strengths of jet velocity and channel flow determine the combined thermal performance. The fluid compressibility is seen to have insignificant effect on the synthetic jet behaviour within the examined range of parameters. As for geometrical parameters, reduced orifice width increases jet velocity improving heat transfer rates while the optima is identified for the heater -to- orifice distance within 6 to 10 times the orifice width.Results conclusively show that in a stagnant fluid medium, the proposed synthetic jet mechanism delivers 40 percent higher heat transfer rates than an equivalent continuous jet. It also thermally outperforms pure natural convection at the heated channel wall by up to 120 times within the parametric range. Under cross-flow conditions, the synthetic jet can provide 2-fold improvement in heat transfer compared to an equivalent continuous jet. By adding this synthetic jet mechanism to a flow channel, the overall thermal performance of the hybrid system is enhanced up to about 18 times the pure forced convection heat transfer rates in a channel without this jet mechanism.The observed outstanding thermal performance of the pulsed jet-cross flow hybrid mechanism surpasses the heat removal potential of current conventional techniques for electronic component cooling. It operates with a unique ability of not causing flow pressure drop increases and not requiring additional fluid circuits, which are recognised as key advantages that set this method apart from other techniques. Thus, the proposed synthetic jet-cross flow hybrid mechanism is envisaged to be potentially regarded as an outstanding thermal enhancement strategy in the development of heat sinks for future high-capacity electronic cooling needs.